Review of the species of Stenothemus from Southeast China (Coleoptera, Cantharidae) - Yang, Yuxia; Ge, Shujuan; Yang, Xingke; Liu, Haoyu (European Journal of Taxonomy, 2021)
The species of Stenothemus Bourgeois, 1907 from Southeast China are reviewed. Stenothemus fukienensis Wittmer, 1974 and S. kuatunensis Wittmer, 1979 are supplementarily described. Two new species are described, S. longicornis Y. Yang & H. Liu sp. nov. (China: Guangdong) and S. flavus Y. Yang & X. Yang sp. nov. (China: Zhejiang). Five new combinations are established: S. biimpressiceps (Pic, 1930) comb. nov. (from Cantharis L.), S. chinensis (Wittmer, 1982) comb. nov., S. limbatipennis (Pic, 1926) stat. rev. et comb. nov., S. nigriceps (Wittmer, 1955) comb. nov. and S. pallicolor (Wittmer, 1951) comb. nov. (from Lycocerus Gorham). Leiothorax atrosanguineus Švihla, 2005 syn. nov. is synonymized with S. chinensis, Lycocerus limatus Kazantsev, 2007 syn. nov. with S. limbatipennis. The above species are illustrated with habitus photos, aedeagi, abdominal sternites VIII and internal genitalia of female. A key for the identification of the above species is provided.